Telemedicine for Retinopathy of Prematurity in 2020. (November 2019) - Bowe, Theodore; Ung, Cindy; Campbell, J. Peter; Yonekawa, Yoshihiro
Purpose: Retinopathy of prematurity (ROP) is the leading cause of visual impairment in premature infants, and middle-income nations are currently experiencing the "third epidemic" of ROP. Screening programs are essential to prevent negative visual outcomes, but screening efforts require a great amount of resources from healthcare systems and are difficult to marshal, particularly in geographically isolated or resource-limited settings. Telemedical screening programs using remote digital fundus imaging (RDFI) systems hold the promise of alleviating many of the burdens that currently make screening for ROP logistically challenging. Methods: Literature review of the current evidence for RDFI telescreening for ROP, with editorial discussion and recommendations. Results: In this review, we summarize the robust body of literature regarding the efficacy of RDFI, the feasibility of telescreening programs, and experiences from current live telescreening programs. We discuss the strengths and limitations of the current evidence and of the screening programs and consider the best practices in developing de novo telemedical screening programs for ROP. The review concludes with a discussion of promising future areas of research and development. Conclusions: RDFI ROP screening programs can be accurate and reliable. They show promise in improving many current challenges in screening infants for ROP, may be able to improve some aspects of care, and have been demonstrated to be cost-effective.